Experimental and Numerical Analysis of Expanded Pipe using Rigid Conical Shape - Ahmed Ibrahim Razooqi (Journal of Engineering, 2018)
The experimental and numerical analysis was performed on pipes suffering large plastic deformation through expanding them using rigid conical shaped mandrels, with three different cone angles (15◦, 25◦, 35◦) and diameters (15, 17, 20) mm. The experimental test for the strain results investigated the expanded areas. A numerical solution of the pipes expansion process was also investigated using the commercial finite element software ANSYS. The strains were measured for each case experimentally by stamping the mesh on the pipe after expanding, then compared with Ansys results. No cracks were generated during the process with the selected angles. It can be concluded that the strain decreased with greater angles of conical shape and an increase in expansion ratio results in an increase of expansion force and a decrease in the pipe thickness and length resulting in pipe thinning and shortening. Good agreement is evident between experimental and ANSYS results within discrepancy (16.90017%) in the X direction and (27.68698%) in the Y direction. Also, the stress distribution is investigated and it can be concluded that the case of Diameter (Do cone) = 35mm and (A) = α = 15° is the optimum.